Cybersecurity in ports: A conceptual approach - Jenna Ahokas; Tuomas Kiiski; Jarmo Malmsten; Lauri M. Ojala (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
As the world is becoming increasingly digitalized, the role of cybersecurity on society is mounting. Recent cyberattacks have showed the vulnerability of critical infrastructure, including ports. The objective is to describe how cybersecurity is perceived in ports, as preparedness and regulation for cyberthreats in ports appears inadequate. The study is a conceptual analysis built upon a comprehensive literature review. The results show that regardless of the growing awareness of the issue, much work needs to be done in order to mitigate the cyberthreats in ports. Situation calls for, among other things, adoption of industry standards and practical level coordination. Cybersecurity in general has been a topical subject, while in the context of ports the theme has thus far been scantly studied. In addition, cybersecurity is currently not included in International Maritime Organization's safety and security Conventions relevant to port, such as ISPS or ISM. Hence this study is among the first openings in its field.
urn:nbn:de:gbv:830-88217481; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; cybersecurity; maritime security; critical infrastructure; ports